The Role of Public Participation on Service Delivery by Public Sector Organizations: The Case of Kenya National Highway Authority - Kabuka, Peter Omae; Nyang’au, Absolom Omariba (HAPSc Policy Briefs Series, 2024)
Worldwide, there are increasingly high expectations when it comes to service delivery. Service delivery is expected both from the public and private sectors. Infrastructure is one of the areas on which citizens rely in their day-to-day activities. Many countries, both developed and developing, are working hard to improve their infrastructure with the objective of achieving this and providing service to their citizens. Kenya’s highways have not achieved the desired milestone. Despite the increased funding, this can be associated with rampant corruption and mismanagement of financial allocations, among others. This has left citizens without the desired services from the Kenya National Highway Authority. Thus, the current study aimed at establishing the role of public participation in service delivery by public sector organizations. A case of Kenya’s national highway authority. The study was guided by two objectives, which include the role of stakeholder engagement in service delivery at the Kenya National Highway Authority and the influence of public involvement in decision-making on service delivery at the Kenya National Highway Authority. The communicative action theory anchored the research. The target population was a total of 118 employees of the Kenya National Highway Authority in the Nairobi region. The sample size of 91 respondents was calculated using Yamane’s 1967 formula. The study used a descriptive research design to examine how the variables were related. The research used a well-structured questionnaire to collect primary data from the respondents. The questionnaire was administered electronically, and the respondents were requested to fill it out and return it. The validity and reliability of the data collection instruments were ascertained using content validity and a pilot test for reliability. Further, a multiple linear regression was done to assess the relationship between the study variables, both independent and dependent variables. Data analysis was done using both descriptive and inferential statistics. Results revealed that public participation improved Service Delivery at the Kenya National Highway Authority. Further, stakeholder engagement will improve service delivery at the Kenya National Highway Authority by 0.420 units, and public involvement in decision-making will improve service delivery at the Kenya National Highway Authority by 0.578 units. In conclusion, the study found that the two variables, stakeholder engagement and Public Involvement in decision-making, significantly explained the service delivery at Kenya’s national highway authority. Thus, the study recommended that there should be active citizen involvement in decision-making as well as stakeholder engagement by providing platforms to establish further areas of expansion for improved service delivery. Further study can be done to explore road safety measures and traffic management strategies implemented by the Kenya National Highway Authority.